Qualitative performance of participated cow for progeny test on smallholder dairy farms - Susilorini Tri Eko; Wahyuni Rini Dwi; Muarifah Hanum; Larasati Rizka; Wicaksono Abimanyu; Indriatmoko Donny Wahyu (BIO Web of Conferences, 2023)
Dairy cow health status affects to milk production and contributes to the profit in many types of dairy management. Locomotion score has been used to determine the qualitative performance score of dairy cows. Investigations on dairy cow located in Wagir Malang were obtained to assess the qualitative performance of participated cow. Selecting participated cow to assure the potential of superior bull from his pedigree in progeny test. There were 85 dairy cows belongs to the smallholder dairy farmer contributed to this research. The result showed that Chest Width 20.99 ± 2.63 cm; Body Depth 79.58 ± 4.79 cm; Rump Angle -2.59 ± 2.43°; Thurl Width 16.46 ± 1.71 cm; Rear Leg Side View 146.82 ± 6.08°; Rear Leg Rear View 15.96 ± 4.19°; Font Foot Angle 42.94 ± 4.81° and Rear Foot Angle 40.12 ± 5.09°. It can be concluded that the qualitative performance of participated cow shows moderate performance based on the standard performance of FH. It is necessary to select the participated cow to improve milk yield of its pedigree and qualitative performance score can be used as the basis of breeding program.